PELATIHAN LITERASI DIGITAL KARANG TARUNA DESA SRIHARJO - Andriyani, Andriyani; Tiyasari, Sindi; Rahmawati, Lia; Nurvitasari, Ika; Jusiputri, Novitasari (EJOIN : Jurnal Pengabdian Masyarakat, 2024)
This Prodamat activity aims to provide digital literacy training for Karang Taruna Sriharjo Village, Bantul, Yogyakarta. The methods for implementing this Prodamat activity are socialization on the introduction of the concept of digital literacy, training on the use of various digital programs and applications for youth, and evaluation of training activities for Karang Taruna. The evaluation results show the effectiveness of implementing digital literacy training as indicated by high ratings from the training participants in terms of aspects of increasing participation in youth digital literacy programs, increasing understanding of digital literacy, utilization of digital literacy applications, applicable training materials, and interactive presentation of material